2010
DOI: 10.1007/s13213-010-0068-6
|View full text |Cite
|
Sign up to set email alerts
|

PCR methods for the detection of biogenic amine-producing bacteria on wine

Abstract: Biogenic amines are low molecular weight organic bases frequently found in wine. Several toxicological problems resulting from the ingestion of wine containing biogenic amines have been described. In wine, histamine, tyramine, and putrescine are mainly produced by the decarboxylation of the amino acid histidine, tyrosine, and ornithine, respectively, by lactic acid bacteria action. The bacterial ability to decarboxylate amino acids is highly variable, and therefore the detection of bacteria possessing amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 40 publications
0
9
0
2
Order By: Relevance
“…By using this method, four strains of acetic acid bacteria could be distinguished. Landete et al (2011) reviewed different molecular methods for the direct detection of biogenic amine-producing bacteria on wine. These methods were based mainly on the detection of certain decarboxylase genes.…”
Section: Resultsmentioning
confidence: 99%
“…By using this method, four strains of acetic acid bacteria could be distinguished. Landete et al (2011) reviewed different molecular methods for the direct detection of biogenic amine-producing bacteria on wine. These methods were based mainly on the detection of certain decarboxylase genes.…”
Section: Resultsmentioning
confidence: 99%
“…lactis , all lactic acid bacteria strains did not any ability to produce histamine in lysine decarboxylase broth. In recently studies, it has been reported that some lactic acid bacteria strains such as Oenococcus oeni and Lactobacillus hilgardii , retain or lose their histamine producing ability depending on the culture conditions since the gene involved in histamine production is located on an unstable plasmid, suggesting a cause for the great variability of the histamine production property among lactic acid bacteria (Lucas and others 2005, 2008; Landete and others 2011).…”
Section: Resultsmentioning
confidence: 99%
“…These amines have been correlated with the spoilage of some foods, such as fish, meat and vegetables (Riebroy et al 2004), although with no toxic effect for consumers. However, they do increase the adverse effects of other amines, such as histamine and tyramine by competing for the detoxifying enzymes (Landete et al 2011) and by reacting with nitrite to produce carcinogenic nitrosamines (Yurchenko and Mölder 2007). There is evidence that putrescine could play a role in promoting the malignancy of adenomas in murine models (Ignatenko et al 2006).…”
Section: Biogenic Aminesmentioning
confidence: 99%